2019
DOI: 10.1371/journal.pone.0223339
|View full text |Cite
|
Sign up to set email alerts
|

In vivo clearance of nanoparticles by transcytosis across alveolar epithelial cells

Abstract: Nanoparticles in polluted air or aerosolized drug nanoparticles predominantly settle in the alveolar lung. Here, we describe a novel, highly effective pathway for the particles to cross the alveolar epithelium and reach the lymph and bloodstream. Amorphous silica nanoparticles, suspended in perfluorocarbon, were instilled into the lungs of mice for intravital microscopy. Particles formed agglomerates that settled on the alveolar wall, half of which were removed from the lung within 30 minutes. TEM histology sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…alveolar epithelium into the bloodstream. [284] In summary, these IVM studies clearly demonstrated that different routes of administration contribute to differential NP distribution at a single-cell level. Future IVM studies will continue to reveal the biological principles behind this differential distribution, and allow researchers to ascertain the optimal routes of administration for different types of NPs.…”
Section: Imaging Pk and Biodistribution Of Materials In The Heart And Lungmentioning
confidence: 70%
See 1 more Smart Citation
“…alveolar epithelium into the bloodstream. [284] In summary, these IVM studies clearly demonstrated that different routes of administration contribute to differential NP distribution at a single-cell level. Future IVM studies will continue to reveal the biological principles behind this differential distribution, and allow researchers to ascertain the optimal routes of administration for different types of NPs.…”
Section: Imaging Pk and Biodistribution Of Materials In The Heart And Lungmentioning
confidence: 70%
“…[283] Finally, IVM has been used to track the movement of inhaled nanoparticulates from the alveoli to the blood stream. [284][285][286] In particular, Detampel et al found that silica NPs can form aggregates on the alveolar wall, resulting in the trapping of the NPs in the alveoli. Time-lapse imaging showed that a large portion of these aggregates were removed from the alveoli in 30 min and found to accumulate subsequently inside the clearance organs.…”
Section: Imaging Pk and Biodistribution Of Materials In The Heart And Lungmentioning
confidence: 99%
“…Smaller agglomerates were observed to disappear quickly, whereas larger entities experienced a gradual reduction in size. A fraction of particle agglomerates remained stationary within the observation timeframe of 1 h, suggesting a second, slower phase of clearance [47] .…”
Section: Intravital Imaging To Answer Fundamental Questions About Nanmentioning
confidence: 94%
“…), Tumour endothelial cells (GSL1-Cy3) (intra-endothelial) [9] Liposomes Organic DiD, DiO Spherical 109±28 PEG Neutral Macropleakages were not stable in space and time (i.v. ), Tumour endothelial cells (CD31)-Neutrophils (Ly6G) [53] SiO2 nanoparticles Inorganic Pacific blue Spherical 70 PEG n/a Macrophages: within minutes Scavenger endothelial cells: with a time scale of hours in transgenic zebrafish embryos( fli1a:eGFP/mpeg1:mCherry ) [54] Amorphous silica nanoparticles Inorganic Red (569 / 585) Spherical 50 n/a Negative 2 min, 1 h after instillation, alveolar epithelial cells [47] Fe 3 O 4 nanoparticles Inorganic Cy5 Cube, Cluster 140 PEG Negative Within 60 min (i.v. ), Renal tubular epithelial cells [48] PLGA based nanoparticles Organic Cy5 Spherical 347.6 ± 21.0 PEG −19.0 ± 0.3 72 h after injection (i.v.…”
Section: Intravital Imaging To Answer Fundamental Questions About Nanmentioning
confidence: 99%
“…This speed and efficiency of removal of the ASN particles does not match the kinetics of alveolar macrophage clearance 8 , which takes weeks to years to complete for other nanoparticles 9 , 10 . Our recent study in mice instilled with labeled ASN, using intravital- and electron microscopy demonstrated that the first phase of the rapid ASN clearance is linked to their crossing of the AEC layer 11 . Silica- and other nanoparticles in the alveolar lumen form agglomerates, as is common for particles of this size in aqueous suspensions 12 .…”
Section: Introductionmentioning
confidence: 97%